A comprehensive temperature-dependent impedance spectroscopy of dielectric behavior and AC conduction in Engineered Multi-Doped Oxide/Si Interfaces - Bengi, Seda; Yeriskin, Seckin Altindal; Cetinkaya, Hayriye Gokcen; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2026)
This study presents a comprehensive investigation of the dielectric-behavior, electric modulus response, AC conductivity, impedance, and phase angle of Al/(Zn: Cd: Ni: TiO2)/p-Si MIS structures over the temperature range of 110-350 K and a bias interval of +/- 3 V, using impedance spectroscopy at 1 MHz. The real (epsilon ') and imaginary (epsilon '') parts of the dielectric constant were extracted from detailed capacitance and conductance measurements, demonstrating a clear dependence on both temperature and applied voltage. The increase in epsilon ' and epsilon '' with rising temperature and forward bias is attributed to enhanced interfacial-polarization, dipolar reorientation, space-charge effects, and thermally activated carriers. The electric modulus formalism, employed to analyze relaxation dynamics and suppress electrode polarization, revealed that the real part (M ') decreases with increasing temperature in both depletion and accumulation regions, while the imaginary part (M '') exhibits temperature-dependent peaks, indicative of dielectric relaxation and redistribution of interface states. The results suggest that short-range charge-transport and localized polarization dominate the dielectric response in different regimes of the applied field. Furthermore, the AC conductivity (sigma(AC)) increases with temperature, exhibiting an Arrhenius-type behavior. Two activation energies, approximately 5.6 meV at low temperatures and 18.9 meV at higher temperatures, were identified, implying the coexistence of distinct conduction mechanisms: shallow trap-assisted hopping at low temperatures and thermally activated carrier mobility at higher temperatures. These findings provide insights into the charge transport and polarization mechanisms governing the dielectric properties of Zn: Cd: Ni-doped TiO2-based MIS structures.
Keywords: Zn:Cd:Ni-doped TiO2; Temperature dependence; Dielectric behavior; Electric modulus; AC conductivity